Mobile Entrepreneurship and Employment - Andjelkovic, Maja; Imaizumi, Saori (MIT Press, 2014)
Given its strong recent growth, the global mobile industry is now a major source of employment opportunities. Mobile industry jobs can be categorized into direct and indirect ones, with a diverse labor force supplying each category. Direct jobs are created by mobile operators and manufacturers in professions that range from engineers to managers to sales support staff. The International Telecommunication Union (ITU) estimates that around 1.5 million people are directly employed in the industry worldwide (ITU 2011). The total number of jobs fitting this narrow “direct” description may begin to decline as the industry becomes commoditized. Indirect jobs, however, show strong potential for growth, in professions related to mobile application development, content provision, and call center operations. Indirect jobs can be created by mobile operators and manufacturers, as well as by third-party content and device producers, including entrepreneurs. In some emerging markets, outsourcing of mobile content development also creates significant numbers of indirect jobs. In India, the mobile industry is expected to generate around seven million indirect jobs during 2012 (COAI 2011). This report argues that faster mobile networks and more capable smartphones make mobile communications a platform for innovation across different sectors (such as health, agriculture, and financial services), supporting overall employment numbers in an economy. The greatest potential for employment growth derives from demand for services enabled by mobile phones.